2012
DOI: 10.2459/jcm.0b013e3283569b24
|View full text |Cite
|
Sign up to set email alerts
|

Four polymorphisms of cholesteryl ester transfer protein gene and coronary stenosis in a Tunisian population

Abstract: The Q allele of the R451Q polymorphism was associated with decreased HDL-C, increased ApoB concentrations and increased risk of coronary stenosis. In haplotype analysis, we found that 1112 seems to be a protective haplotype, whereas 2111 has an atherogenic effect in a coronary Tunisian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This trend of association was consistent in all ethnic groups and genders although statistical significance was attained only in the Chinese men. Significant association of the B2 allele with elevated HDL-C was also reported for the Framingham population [11], Chinese population [23], Iranian population [19,20] and Tunisian population [9]. In their studies, the protective effects of the B2 allele on the development of CAD were observed in association with increased HDL-C and decreased CETP activity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This trend of association was consistent in all ethnic groups and genders although statistical significance was attained only in the Chinese men. Significant association of the B2 allele with elevated HDL-C was also reported for the Framingham population [11], Chinese population [23], Iranian population [19,20] and Tunisian population [9]. In their studies, the protective effects of the B2 allele on the development of CAD were observed in association with increased HDL-C and decreased CETP activity.…”
Section: Discussionmentioning
confidence: 79%
“…CETP facilitates the transfer of cholesteryl ester from HDL to triglyceride-rich lipoproteins in exchange for triglycerides (TG) [5,6]. Many CETP DNA polymorphisms that may alter the function of CETP have been reported [7-9]. However, the association of these polymorphisms with phenotypes such as lipid levels and the CAD remain inconsistent [10-14].…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in the CETP gene that determine decreased CETP activity and/or mass are associated with elevated concentrations of HDL-c and decreased CVD risk [4]. A number of SNPs have been described in the CETP gene (Accession id: ENSG00000087237) [10]- [12]. Most of these SNPs are associated with low plasma CETP protein and high HDL-c concentrations in plasma [10] [13].…”
Section: Introductionmentioning
confidence: 99%
“…The rs5882 SNP has been associated with lower CETP serum concentrations and activity, increased HDL cholesterol levels, and increased lipoprotein sizes, all factors which have been associated with a lower CVD risk [16]. In a recent study in Tunisian population, there was no statistically significant association of the rs5882 SNP with lipoprotein metabolism or atherogenicity [17]. …”
Section: Discussionmentioning
confidence: 99%